Energy Access, Poverty, and Development : The Governance of Small-Scale Renewable Energy in Developing Asia /: The Governance of Small-Scale Renewable Energy in Developing Asia. (2016) - Sovacool, Benjamin K; Drupady, Ira Martina
No abstract available